2021
DOI: 10.1002/jimd.12404
|View full text |Cite
|
Sign up to set email alerts
|

OTC deficiency in females: Phenotype‐genotype correlation based on a 130‐family cohort

Abstract: OTC deficiency, an inherited urea cycle disorder, is caused by mutations in the X‐linked OTC gene. Phenotype‐genotype correlations are well understood in males but still poorly known in females. Taking advantage of a cohort of 130 families (289 females), we assessed the relative contribution of OTC enzyme activity, X chromosome inactivation, and OTC gene sequencing to genetic counseling in heterozygous females. Twenty two percent of the heterozygous females were clinically affected, with episodic (11%), chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…It has been suggested that disease presentation in females results from skewed patterns of X-inactivation affecting expression of a wild type and a severe pathogenic SNP. 3739 We therefore examined the behavior in our assay of amino acid substitutions corresponding to SNPs falling into these three groups (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that disease presentation in females results from skewed patterns of X-inactivation affecting expression of a wild type and a severe pathogenic SNP. 3739 We therefore examined the behavior in our assay of amino acid substitutions corresponding to SNPs falling into these three groups (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that disease presentation in females results from skewed patterns of X-inactivation affecting expression of a wild type and a severe pathogenic SNP. [37][38][39] We therefore examined the behavior in our assay of amino acid substitutions corresponding to SNPs falling into these three groups (Figure 8). The distributions of amino acid substitutions corresponding to neonatal and female variants were very similar and associated with severe loss of activity in our assay (Figure 9).…”
Section: Variant Assay Values Agree Closely With Otc Clinical Stratif...mentioning
confidence: 99%
“…[ 9 ] Due to the random pattern of X-chromosome inactivation in hepatocytes, approximately 20% of heterozygous females are symptomatic with highly variable age of onset and clinical features. [ 10 ] Acute hyperammonemic decompensations can be precipitated by stressors and become a life-threatening event at any age and any stage of the disease. [ 9 , 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Severe deficiencies are more common in males and typically present in the neonatal period, with serious consequences for hyperammonemia and a risk of permanent neurological damage. Partial deficiencies have the greatest possible clinical spectrum and are common in heterozygous females [ 4 ]. In female carriers, severe symptoms in childhood are rare; up to 20% can experience mild symptoms, and some individuals do not experience any symptoms until a stressor, such as pregnancy or delivery, triggers an acute episode of hyperammonemia [ 3 ].…”
Section: Introductionmentioning
confidence: 99%